Applied structural equation modelling for researchers and practitioners : using R and Stata for behavioural research - Ramlall, Indranarain (Bingley : Emerald Group Publishing Limited, 2016)
During the last two decades, structural equation modelling (SEM) has emerged as a powerful multivariate data analysis tool in social science research settings, especially in the fields of sociology, psychology, and education. Social science researchers and students benefit greatly from acquiring knowledge and skills in SEM, since the methods can provide a bridge between the theoretical and empirical aspects of behavioural research. Ramlall explains in a rigorous, concise, and practical manner all the vital components embedded in structural equation modelling (SEM). Focusing on R and Stata to implement and perform various structural equation models, Ramlall examines the types, benefits, and drawbacks of SEM, delving into model specifications and identifications, fit evaluations, and path diagrams.
Includes bibliographical references.
Print version record
Keywords: Structural equation modeling; Education -- Teaching Methods & Materials / Social Science; Sociology